Perancangan Alat Bantu Pengendalian Kualitas Shuttle Cock Secara Atribut Dan Variabel Dengan Pendekatan Antropometri Pada Industri Kecil Di Kelurahan Serengan - Eko Liquiddanu; Taufiq Rochman; Akung Purwito Aji (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2007)
Serengan is the center of shuttle cocks small scale industry in Surakarta. The makers use simple tools to process the shuttle cocks. Besides, there are no tools to control which are used to inspect the shuttle cocks in the making process or as the final products. This condition makes the customers get no guarantee for the shuttle cocks they buy, especially the shape of the shuttle cocks. In this research, the quality variables measured were the length of the feather, the height and diameter of the cork. So that, the tools to control the quality of shuttle cocks are needed to standardize the quality of the shuttle cocks produced. In this research, the setting up of shuttle cock’s quality control tools atributely and variably were done by using anthropometry approach. The product samples of the shuttle cock were taken from the makers especially T3 brand. The sample were used to know how far the process deviation by using x and R diagrams and the analysis of process ability was done to find out the process distribution to product specification. The shuttle cock’s quality control tools were designed by using anthropometry approach. The anthropometry data were collected from the measurement of the students of Industrial Engineering of Sebelas Maret University at The Laboratorium of Work Design and Ergonomy Analysis of Industrial Engineering Sebelas Maret University. The data processing result shows that the length of feather, the height and the diameter of the cork, especially T3 brand, are still out of the limit of specifications. Then, the tools to control the quality of the shuttle cocks based on their feather’s length and the cork’s height and diameter was designed. The tools were designed based on anthropometry approach by measuring the quality atributely and variably wich can determine whether a product can pass the specification or not based on variables measured.